"Yes, We Do Want to Subvert and Corrupt Young People": Thee Temple ov Psychick Youth Against the Mainstream Media - Consenstein, Eden (Nova religio, 2022)
In 1992, the British television news program Dispatches aired clips from a video described as the first ever, eyewitness proof of satanically motivated child abuse. Days later, newspapers reported that the video was misrepresented. The clips were drawn from First Transmissions, an experimental video produced by Thee Temple ov Psychick Youth (T.O.P.Y.) a geographically disperse occult collective committed to subverting mainstream media. This article provides a detailed history of this incident. First, it uses the event as an entrée into T.O.P.Y.'s magickal media activism. Second, it locates the groups' inadvertent appearance on Dispatches within sweeping changes to the late-20th-century media landscape. Providing this context demonstrates how new possibilities in the production and circulation of audiovisual media provoked religious conflicts and concerns for radical occultists and conservative television journalists alike. While T.O.P.Y.'s uses of media were intended to enable individual self-actualization and to undermine established institutions, their detractors on Dispatches figured underground media economies as sites of satanic conspiracy and worked to discipline their creators.